Slit/Robo Signaling Regulates Multiple Stages of the Development of the Drosophila Motion Detection System - Guzmán-Palma, Pablo; Contreras, Esteban G.; Mora, Natalia; Smith, Macarena; González-Ramírez, M. Constanza; Campusano, Jorge M.; Sierralta, Jimena; Hassan, Bassem A.; Oliva, Carlos (Frontiers in Cell and Developmental Biology, 2021)
Neurogenesis is achieved through a sequence of steps that include specification and differentiation of progenitors into mature neurons. Frequently, precursors migrate to distinct positions before terminal differentiation. The Slit-Robo pathway, formed by the secreted ligand Slit and its membrane bound receptor Robo, was first discovered as a regulator of axonal growth. However, today, it is accepted that this pathway can regulate different cellular processes even outside the nervous system. Since most of the studies performed in the nervous system have been focused on axonal and dendritic growth, it is less clear how versatile is this signaling pathway in the developing nervous system. Here we describe the participation of the Slit-Robo pathway in the development of motion sensitive neurons of the Drosophila visual system. We show that Slit and Robo receptors are expressed in different stages during the neurogenesis of motion sensitive neurons. Furthermore, we find that Slit and Robo regulate multiple aspects of their development including neuronal precursor migration, cell segregation between neural stem cells and daughter cells and formation of their connectivity pattern. Specifically, loss of function of slit or robo receptors in differentiated motion sensitive neurons impairs dendritic targeting, while knocking down robo receptors in migratory progenitors or neural stem cells leads to structural defects in the adult optic lobe neuropil, caused by migration and cell segregation defects during larval development. Thus, our work reveals the co-option of the Slit-Robo signaling pathway in distinct stages neural lineage development.